2016
DOI: 10.2214/ajr.14.13923
|View full text |Cite
|
Sign up to set email alerts
|

Use of DWI in the Differentiation of Renal Cortical Tumors

Abstract: OBJECTIVE The purpose of this study was to differentiate clear cell renal cell carcinoma (RCC) from other common renal cortical tumors by use of DWI. MATERIALS AND METHODS The study included 117 patients (mean age, 60 years) with 122 histopathologically confirmed renal cortical tumors who underwent 1.5-T MRI that included DWI before they underwent nephrectomy between 2006 and 2013. For each tumor, two radiologists independently evaluated apparent diffusion coefficient (ADC) values on the basis of a single RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 33 publications
2
35
1
3
Order By: Relevance
“…A few reports recommend that ADC might be related well with morphologic and histologic prognostic parameters in RCC [7]. Thus, the minimum ADC was observed to be an independent factor for recurrence of RCC after nephrectomy [8].…”
Section: Introductionmentioning
confidence: 93%
“…A few reports recommend that ADC might be related well with morphologic and histologic prognostic parameters in RCC [7]. Thus, the minimum ADC was observed to be an independent factor for recurrence of RCC after nephrectomy [8].…”
Section: Introductionmentioning
confidence: 93%
“…From the enhancement pattern, pRCC can be differentiated from ccRCC with 93% sensitivity and 96% specificity [60]. ADC values are described to be higher compared with ccRCC [63]. Based on MR imaging findings, type 1 and 2 pRCCs cannot be differentiated [44].…”
Section: Papillary Rccmentioning
confidence: 99%
“…The tumors are hypovascular and show less contrast enhancement in all phases compared with the renal cortex [64]. Although conflicting results have been reported, a meta-analysis showed that differentiation of oncocytoma from RCC based on ADC values is feasible [55,63]. However, great heterogeneity exists in the scanning protocols and b-values, making these results hard to reproduce.…”
Section: Oncocytomamentioning
confidence: 99%
“…Mittels Chemical-Shift(CSI)-Sequenzen lässt sich mikroskopisches Fett nachweisen [30]. Der "apparent diffusion coefficient" (ADC) des klarzelligen RCC ist gemeinhin höher als in anderen RCC-Subtypen [15]. Ein inverser Zusammenhang zwischen dem ADC und dem FuhrmanGrad wurde berichtet [8].…”
Section: Klarzelliges Rccunclassified
“…Nach Kontrastmittel(KM)-Applikation (e, koronare T1w mit Fettsättigung) zeigt sich der solide Anteil kontrastmittelaffin, während der fettige Anteil signalsupprimiert ist. In der korrespondierenden KM-verstärkten Computertomografie (f arterielle Phase, g venöse Phase) zeigt der solide Anteil eine kräftige initiale Anreicherung mit Wash-out, der fettige Anteil ist annähernd isodens zum umgebenden Fettgewebe hilfreich, beide Entitäten weisen eher hö-here ADC-Werte auf [15,39].…”
Section: Onkozytomunclassified